Visualizing, measuring and managing knowledge - Bukowitz, Wendi R.
Wendi R. Bukowitz and Gordon P. Petrash present principles for effectively managing a company's intellectual assets.
With the renewal and deployment of intellectual assets emerging as a critical corporate competency, Dow Chemical, Skandia and Buckman Labs are creating measurement systems to improve how they manage their own 'intangibles.'
As companies continue to trade at many multiples of their book value, executives are beginning to look for ways to manage and measure the intangible assets that are increasingly recognized as large contributors to their organization's market value. Companies such as The Dow Chemical Company, Skandia and Buckman Laboratories International are developing measurement systems to assess how well they leverage organizational knowledge to create value for customers, which is ultimately reflected in stock prices. These organizations are developing measurement systems for intangibles that can : 1) align individual actions with organizational strategy, and 2) anticipate positive as well as negative financial outcomes in enough time to enhance the former and possibly avoid the latter altogether.
Keywords: Knowledge management